2017
DOI: 10.3390/ma10080852
|View full text |Cite
|
Sign up to set email alerts
|

Production of High-Value Nanoparticles via Biogenic Processes Using Aquacultural and Horticultural Food Waste

Abstract: The quantities of organic waste produced globally by aquacultural and horticulture are extremely large and offer an attractive renewable source of biomolecules and bioactive compounds. The availability of such large and diverse sources of waste materials creates a unique opportunity to develop new recycling and food waste utilisation strategies. The aim of this review is to report the current status of research in the emerging field of producing high-value nanoparticles from food waste. Eco-friendly biogenic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(27 citation statements)
references
References 143 publications
(162 reference statements)
1
26
0
Order By: Relevance
“…This finding is in accordance with preceding reports relating to ZnO and alumina NPs biosynthesis using potato and algal extracts [55,56]. Likewise, Poinern et al indicated that various bioactive compounds present in food waste are key responsible materials for bioreduction metal ions and stabilization of metallic NPs [57].…”
Section: The Mechanism For the Formation Of Cuo Nanoparticlesupporting
confidence: 93%
“…This finding is in accordance with preceding reports relating to ZnO and alumina NPs biosynthesis using potato and algal extracts [55,56]. Likewise, Poinern et al indicated that various bioactive compounds present in food waste are key responsible materials for bioreduction metal ions and stabilization of metallic NPs [57].…”
Section: The Mechanism For the Formation Of Cuo Nanoparticlesupporting
confidence: 93%
“…Multiple biological actions of the NPs such as antibacterial [ 2 , 3 ], antioxidant [ 2 , 4 ], anticancer [ 5 , 6 ], antifungal [ 5 , 7 ], antiviral [ 8 , 9 ], antiparasitic [ 10 , 11 ] and anti-inflammatory activities [ 12 , 13 ] have been associated with their highly diverse chemistry-rich characteristics [ 14 ]. There are myriad ways of synthesizing NPs, including physical (e.g., vapor deposition [ 15 ], sputter deposition [ 16 ], electric arc deposition [ 17 ], ion beam technique [ 18 ], molecular beam epitaxy [ 19 ], melt mixing [ 20 ]), chemical (e.g., co-precipitation [ 21 ], sol-gel [ 22 ], microemulsions [ 23 ], sonochemical synthesis [ 24 ] UV-initiated photoreduction [ 25 ]), and biological (e.g., synthesis using plant extracts [ 26 ], microorganisms [ 26 ], algae [ 27 ], fungi [ 28 ], animals [ 29 ] or agricultural waste [ 30 ], enzymes [ 31 ]) methods as well as hybrid methods [ 32 ] ( Figure 1 ). There are advantages and limitations for each synthetic method, and the choice of method is selected based on the downstream applications.…”
Section: Nanoparticles and Green Technologymentioning
confidence: 99%
“…[15,111]. The bacteria are known to synthesize metallic nanoparticles by either intracellular or extracellular mechanisms [123]. Even though bacteria-mediated nanoparticle biosynthesis is known to produce less toxic metal oxide nanoparticles, such as CuO, TiO 2 , ZnO, and iron oxide, it involves fastidious cell culturing alongside difficulties in controlling the size distribution, shape and crystallinity of many metal oxide nanoparticles [44].…”
Section: Bacteria Mediated Biosynthesis Of Metal Oxide Nanoparticlesmentioning
confidence: 99%